Late Miocene and early Pliocene biosiliceous sedimentation along the California margin - John A. Barron; Mitchell Lyle; Itaru Koizumi (Revista Mexicana de Ciencias Geológicas)
Biogenic opal sedimentation is compared between offshore and onshore areas of the California margin during the late middle Miocene, the late Miocene, and the early Pliocene. The records from offshore ODP Sites 1010 and 1021 have declining opal abundance, with a dramatic three-fold decline at about 11.5 Ma and a second, less pronounced drop occurring at about 7.6 Ma. Thick stratigraphic sections of diatomaceous sediments dated between 11.5 and 10.0 Ma and between 7.6 and 6.5 Ma are found onshore in California, whereas coeval intervals in offshore deep sea sites display relatively low opal percentages. This suggests that during periods of reduced strength in the California Current, diatom production declined in offshore areas while it increased in more coastal regions. The early Pliocene and early part of the late Pliocene (4.6 to ca. 2.7 Ma) are marked by the near absence of diatoms in offshore sites, while diatoms are masked by clastic components in onshore sections. Diatom production was greatly reduced along the California margin during this climatically warm period of the Pliocene at the same time that production dramatically increased in the subarctic northwest Pacific, suggesting fractionation of opal to higher latitudes.